Interaksi Sosial Pemeluk Antar Agama: Studi Kasus di Desa Balerejo Wlingi Blitar - Salimatul Intiha'iyah; Ahmad Nurcholis (Pascasarjana IAIN Sultan Amai Gorontalo, 2024)
This research discusses community interaction in a village with various religions, thus creating a culture by the characteristics of Indonesian society. This research uses George Herbert Mead's mind, self, and society theory. The method used is qualitative research with a case study approach. Data collection techniques were observation, documentation, and interviews. The results showed that the Balerejo Village community is a plural society, that respects and appreciates differences, they realize it by holding celebrations of several religions that are celebrated together, they also closely maintain unity and integrity which is realized through cooperation. Leadership in this village is also important in realizing several activities. Islam as the majority religion also has several activities that other villagers commonly carry out. In addition, the Balerejo Village community is a community that still upholds the ancestral values of Javanese society.